Migraine biomarkers in cerebrospinal fluid: A systematic review and meta-analysis. (January 2017) - van Dongen, Robin M; Zielman, Ronald; Noga, Marek; Dekkers, Olaf M; Hankemeier, Thomas; van den Maagdenberg, Arn MJM; Terwindt, Gisela M; Ferrari, Michel D
Objective: To perform a meta-analysis of migraine biomarkers in cerebrospinal fluid (CSF) and of corresponding blood concentrations. Methods: We conducted a systematic search for studies that measured biochemical compounds in CSF of chronic or episodic migraineurs and non-headache controls. Subsequent searches retrieved studies with blood measurements of selected CSF biomarkers. If a compound was assessed in three or more studies, results were pooled in a meta-analysis with standardised mean differences (SMD) as effect measures. Results: Sixty-two compounds were measured in 40 CSF studies. Most important results include: increased glutamate (five studies, SMD 2.22, 95% CI: 1.30, 3.13), calcitonin gene-related peptide (CGRP) (three studies, SMD: 3.80, 95% CI: 3.19, 4.41) and nerve growth factor (NGF) (three studies, SMD: 6.47, 95% CI: 5.55, 7.39) in chronic migraine patients and decreased β-endorphin (β-EP) in both chronic (four studies, SMD: –1.37, 95% CI: –1.80, –0.94) and interictal episodic migraine patients (three studies, SMD: –1.12, 95% CI: –1.65, –0.58). In blood, glutamate (interictal) and CGRP (chronic, interictal and ictal) were increased and β-EP (chronic, interictal and ictal) was decreased. Conclusions: Glutamate, β-EP, CGRP and NGF concentrations are altered in CSF and, except for NGF, also in blood of migraineurs. Future research should focus on the pathophysiological roles of these compounds in migraine.